EFIKASI DIRI, DUKUNGAN SOSIAL KELUARGA DAN SELF REGULATED LEARNING PADA SISWA KELAS VIII - Adicondro, Nobelina; Purnamasari, Alfi (Universitas Ahmad Dahlan, 2011)
The purposes of this study were to find out (1) the relation betweenself efficacy, family social support and self regulated learning (2) the relationbetween self efficacy and self regulated learning (3) the relation betweenfamily social support and self regulated learning. The populations of thestudy were students of 8th grade students at SMP Muhammadiyah. Thetechnique sampling was cluster random sampling. The study used SelfEfficacy Scale, Family Social Support Scale and Self Regulated LearningScale to collect data about self efficacy, family social support and selfregulated learning. The data were analized by regression analysis. Theresults show that (1) there is very significantly positive correlation betweenself efficacy, family social support and self efficacy (r=0,837, p=0,000),(2) there is very significantly positive correlation between self efficacy andself regulated learning (r=0, 836, p=0,000), (3) there is very significantlypositive correlation between family social support and self regulated learning(r=0,418, p=0,002).